What has Jerusalem to do with Athens? a proposal on the role of theology in the Ateneo de Manila University in the light of Karl Rahner's evolutionary christology - Jimenez, Edilberto C. (Asian Perspectives in the Arts and Humanities, 2011)
This paper proposes a dialogue between the disciplines of theology and the natural sciences, particularly in the topic of the evolutionary understanding of the origin of humanity. The context of this dialogue is the Ateneo de Manila University, a Jesuit and Catholic university, that has among its goals the promotion of academic excellence and the formation of mature Christian faith in its students and faculty: are these two goals mutually exclusive, contradictory, or mutually enriching? The article begins with a brief history of the problematic relationship between theology and science. It then presents the transcendental christology of Karl Rahner that attempts to articulate creation and incarnation in an evolutionary perspective. The article concludes with a proposed definition of the relationship between theology and the natural sciences in the Ateneo de Manila University: theology as a “place of plurality in unity.”